An Offer You Can’t Refuse: Coercing Consent to Surgery through the Medicalization of Gender Identity - Silver, Anne E. (Columbia Journal of Gender and Law, 2014)
Can consent to medical treatment be voluntary when legal rights, benefits, and protections are conditioned on the completion of surgery? This Note will analyze this question by applying the doctrine of informed consent and basic bioethical principles to the “medical model” that has emerged as the dominant method for determining the legal status of transgender and intersex individuals. Under the medical model, reclassification of legal sex—a process that provides access to legal rights, resources, and benefits—is available to trans persons only after the individual has undergone permanent, body-altering surgery. This Note will argue that conditioning legal status on the completion of surgery coerces or manipulates consent in such a manner as to render consent involuntary under the doctrine of informed consent. This Note will suggest alternatives to the medical model that do not violate the doctrine of informed consent and basic bioethical norms.